Pemanfaatan Waktu Luang Peserta Didik Kelas IX Di Luar Jam Sekolah Dalam Meningkatkan Kemampuan BTQ - Nur Ina Fildzha Zahia; Wahyu Hidayat; Sudirman (Dialektika : Jurnal Pendidikan Agama Islam, 2024)
Abstract: Everyone has time to spend doing activities that support their performance or time spent just to entertain and relax. This also applies to students, in addition to time to study at school, they also have free time at home. The results of field observations show that the ability reading and writing skills of the Qur'an some class IX students do not meet the KKM, therefore some improvements are needed in the learning process, one of which is the use of free time outside of school hours and students. Keyword: Free time, parents, students, and ability reading and writing skills of the Qur'an.